Identification and Validation of Ferroptosis-Related Biomarkers in Septic Cardiomyopathy via Bioinformatics Analysis - Gong, Cheng-Wu; Yuan, Ming-Ming; Qiu, Bai-Quan; Wang, Li-Jun; Zou, Hua-Xi; Hu, Tie; Lai, Song-Qing; Liu, Ji-Chun (Frontiers in Genetics, 2022)
Sepsis cardiomyopathy (SCM) is a cardiac dysfunction caused by severe sepsis and septic shock that increases the risk of heart failure and death and its molecular mechanism remains unclear. Ferroptosis, a novel form of programmed cell death, has been reported to be present in the heart tissue of patients with sepsis, which demonstrated that ferroptosis may be a potential mechanism of myocardial injury in SCM. Therefore, we explored the role of ferroptosis-related genes (FRGs) in SCM and aimed to identify pivotal ferroptosis-related biomarkers in SCM and potential therapeutic targets involved in the pathological process of SCM. To explore the regulatory mechanisms of ferroptosis in SCM, we identified differentially expressed genes (DEGs) in SCM and FRGs by bioinformatics analysis, and further identified hub genes. And the crucial microRNAs (miRNAs)-FRGs regulatory network was subsequently constructed. Finally, several candidate drugs associated with the hub genes were predicted, and qRT-PCR and western blotting analysis were performed to confirm the abnormal expression of hub genes. In this study, we identified several FRGs that may be involved in the pathogenesis of SCM, which provide insights for further definition of the role of ferroptosis in SCM and contribute to a deeper understanding of the molecular mechanisms and potential therapeutic targets of SCM.